A study of Helicobacter pylori infection in diabetes mellitus - Zafar, Khwaja Saifullah; Ram, Vidyasagar; Kumar, Manoj (International Journal of Research in Medical Sciences, 2016)
Background: Helicobacter pylori is the most common bacterial infection in human beings. The aim was to study the association of Helicobacter pylori infection in patients of diabetes mellitus. Design of the study was observational analytic cross sectional study. Methods: A total of 69 subjects were studied. Of these 30 were non diabetics and 39 were diabetics, with disease duration more than 1 year. The serological diagnosis of H. pylori was made by Anti- Helicobacter pylori antibody test. Antral biopsies of all diabetic patients were taken during endoscopy and subjected to histological examination. Results: The mean age for the diabetics was 48.9±9.86 years and that of non-diabetics was 47.9±9.16 years. The majority of the subjects belonged to fifth and sixth decades. There was conspicuous male preponderance in both the diabetics and the nondiabetics group, more attributable to the selection bias. Serum samples of all the subjects were tested for the presence of IgG against Helicobacter pylori. Helicobacter pylori was positive in 40% of non-diabetics and 64.1% of diabetics X2 = 3.96, p value=0.047 (p<0.05) i.e. the prevalence of Helicobacter pylori in diabetics is significantly higher than that in non-diabetics. Histological examination of antral biopsies (known to be the gold standard method of diagnosing Helicobacter pylori) was performed in all diabetics and comparison of the type of diabetes, duration of diabetes, and level of glycaemia and complications of diabetes were made in patients of diabetes with and without Helicobacter pylori. This study showed patients with IDDM had higher positivity (75%) than those of NIDDM (67.6%). The mean duration of diabetes with Helicobacter pylori group was 7.85+3.93 years, and higher than that of diabetics without Helicobacter pylori which was 5.83±2.52. The mean fasting blood sugar was 192±60.3 mg/dl in diabetics with Helicobacter pylori group and was higher than that of diabetics without Helicobacter pylori group which was 167±37.1mg/dl. The mean post prandial blood sugar in diabetics with Helicobacter pylori group was 318±78.4mg/dl and was more than that of diabetics without Helicobacter pylori group in whom it was 280±49.7mg/dl. The two diagnostic modalities viz serological and histological identification of Helicobacter pylori correlated well with each other. It was observed that serological diagnosis by Anti- Helicobacter pylori antibody test is 80% sensitive and 75% specific. Conclusions: The prevalence of Helicobacter pylori is higher in diabetics than the non-diabetics. The prevalence of Helicobacter pylori infection had no significant correlation with duration of diabetes, type of diabetes, glycaemia levels of diabetics and complications of diabetics. The serological diagnosis of H. pylori was made by Anti- Helicobacter pylori antibody test, by Biochem Immuno systems ITALIA SPA ELAGEN Helicobacter pylori IgG Kit. This ELISA technique is 80% sensitive and 75% specific.